Impact of Activity Ratio, Profitability, Liquidity, and Asset Structure on Capital Structure in Food and Beverages Companies Listed On Indonesia Stock Exchange Period 2015-2019 - Erni Martini; Muhammad Adyb Ramli; Tieka Trikartika Gustyana; Nugraha Nugraha (Jurnal Manajemen Indonesia, 2021)
This study has an objective to examine the effect form activity ratio (TATO), liquidity (CR), profitability (ROA), and asset structure on capital structure (DER). Data processing uses financial reports from seventeen (17) F&B companies that listed on the Bursa Efek Indonesia (BEI) from period 2015 to 2019. A total of 425 data were used as samples using purposive sampling technique. Data panel regression used to analyze data and testing hypotheses. Results showed the simultaneous influence between the activity, liquidity, profitability, and asset structure to capital structure. Partially, activity ratio and asset structure variable do not affect capital structure. This study also proved that profitability affects capital structure in positive and significant relationship, while liquidity has a negative and significant effect to capital structure. Further findings are discussed in this study. Keywords – activity ratio, asset structure, capital structure, liquidity, profitability